Carragenana acilada como remediadora na adsorção de enzimas em filmes de Lagmuir e Langmuir-Blodgett - Rocha, Jefferson Muniz [UNIFESP] (2015)
Interactions involving lipids, polysaccharides and enzymes are of great interest in biological levels as well as in numerous industrial applications. In this context, the aim of this study was to evaluate the role of an acylated carrageenan (CaA) in the adsorption of enzymes, specifically phosphorylase sucrose (SF), using Langmuir and Langmuir-Blodgett films made of phosphatidic dimeristroil acid (DMPA), which can be understood as bioinspired systems. The incorporation of both carrageenan and enzyme was evaluated by adsorption kinetic curves, surface pressure-area isotherms, Brewster angle microscopy (BAM), quartz crystal microscopy (QCM) and polarization modulation reflection-absorption infrared spectroscopy (PM-IRRAS). The presence of macromolecules incorporated into the lipid monolayer was proved by spectroscopy in the infrared region and by an increase in the surface density with the increase of the applied surface pressure. Also in relation to Langmuir films, it was observed an increase in the stability of monolayers and phase segregation in the presence of CaA. Langmuir-Blodgett films (LB) were deposited on different solid supports and presented more homogeneity in the presence of CaA and enhanced interaction among the components of the films. It was also possible to obtain mass density assigned to CaA and SF and confirm the presence of the immobilized enzyme based on fluorescence spectroscopy analysis. In addition, up to 89% of the enzyme activity on the film remained in relation to the homogeneous environment, determined by UV-Vis spectroscopy, and a higher activity retention for the immobilized enzyme compared to free enzyme in a homogeneous environment. Thus, it was proved the effectiveness of the CaA in the adsorption of the SF enabling the feasibility of the nanostructured film as a possible biosensor.